Parenthood and Men’s and Women’s Gender-Role Attitudes: Does Child’s Gender Matter? - Jarallah, Yara; Baxter, Janeen; Perales, Francisco (Brisbane, 2016)
Gender-role attitudes refer to individuals’ levels of support for a division of labour based on the notion of separate spheres and are closely connected to prevailing gender inequalities at home and at work. Previous research has established that life course transitions are related to within-individual over-time change in gender-role attitudes. Most importantly, becoming a parent is associated with shifts towards more traditional gender-role attitudes. Exposure- and interest-based theories of gender-attitude change suggest that the gender of children should influence the pattern of attitude shifts that accompany parenthood, but few studies have investigated this. We do so using Australian panel data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey (n=14,439 individuals) and panel regression models. We find that men’s and women’s gender-role attitudes become more traditional when they become parents, but find little evidence of variations depending on the gender of their children.
LCC Working Paper Series
Keywords: Gender; Families -- Parents and Parenting; Families and relationships; Gender; Gender; Families; Parents and Parenting; Gender; Families and relationships